Developing human biomonitoring as a 21st century toolbox within the European exposure science strategy 2020–2030 - Zare Jeddi, Maryam (2022)
Funding Information: The authors are grateful to all experts from academia, institutes and industry that have participated in discussions that helped formulate the present strategy paper. They would also like to thank ISES Europe for initiating the discussions to prepare a European Exposure Science Strategy 2030. The German Federal Institute for Occupational Safety and Health (BauA), National Institute for Public Health and the Environment (RIVM) and the European Commission Joint Research Centre (JRC) are also acknowledged for each hosting of a meeting in 2018, 2019 and 2020 respectively during which the foundations of the current strategy were built. The views expressed are those of the authors alone and do not necessarily reflect those of the organisations at which they are employed. Publisher Copyright: © 2022 The Authors